THE USE OF FREEZE FRAMING TECHNIQUE FOR TEACHING ENGLISH TO YOUNG LEARNERS AT TOWN FOR KIDS PRESCHOOL JAMBI - Pretty Elisa Ayu Ningsih (Sekolah Tinggi Pariwisata Mataram, 2020)
This research attempted to describe how the teacher used freeze framing technique engaged the students during the teaching and learning process. It also attempted to describe how the students responded toward the use of this technique. The participants of this research were Kindergarten 1 Pink students. Observation checklists, field note, video recorder and interview protocol were used as the instruments. This research was done as a classroom action research consisted of three cycles. Each cycles conducted in three meetings. In each meeting the researcher implemented the technique while she used video as the media. First, the researcher froze the video and then she asked several questions to the students. The questions were related to the video. She let the students answered freely without judging their answers. After that, she played the video again and let them watched the video to know whether their answers were correct or not. The result of this research showed that the students were engaged actively during the discussion. They were able to answer the teacher’s questions as well as share their ideas. Consequently, Freeze Framing Technique improved the teaching and learning process. The students became more active and involved during the classroom discussion. In conclusion, Freeze Framing Technique was helpful for the teacher in teaching English to young learners